Modification of bauxite residue with oxalic acid for improved performance in intumescent coatings - Arogundade, A.I. (Elsevier Editora Ltda, 2021)
Valorization of bauxite residue (BR) enhances the dynamics of its application in intumescent coating for fire retarding systems. This BR, an alumina production waste could contain up to 45 ferrous oxide along with residual aluminous minerals. In an attempt to optimize the fire retardant properties of these minerals in intumescent systems, BR was treated in oxalic acid, varying the heating temperature between 50 °C and 100 °C at a constant pH of 2.65. X-ray florescence spectrometry revealed up to 80 reduction in iron content and total dissolution of desilication products (DSPs). The process temperature was found to affect the efficiency with which iron oxide was removed and with which the dissolved DSPs were precipitated as aluminum hydrates. X-ray diffraction revealed increased crystallinity and a gibbsite-dominated compound. Incorporation of the modified bauxite residues into a control intumescing formulation resulted in improved endothermic cooling, increased char expansion and char reinforcement. An inverse relationship appeared to exist between aluminum hydrates and iron as removal of iron led to enhanced intumescence and increased char expansion while higher iron content led to a compact, less expanded char. A balance of the fire retarding minerals occurred at a leaching temperature of 75 °C in oxalic acid. Best heat shielding performance thus occurred at XBR75-IC5 as char expansion increased by 12 and the substrate temperature reduced by 31 over the control IC system. Thus, BR may act as alternative fire retardant filler for intumescing systems. © 2021 The Author(s).